Nationwide survey on the management of pediatric pharyngitis in Italian emergency units - Gregorio P. Milani; Claudio Rosa; Naz Tuzger; Ilaria Alberti; Chiara Ghizzi; Stefania Zampogna; Angela Amigoni; Carlo Agostoni; Diego Peroni; Paola Marchisio; Elena Chiappini; IPSE study group (BMC, 2023)
Abstract Background Acute pharyngitis is a frequent reason for primary care or emergency unit visits in children. Most available data on pharyngitis management come from primary care studies that demonstrate an underuse of microbiological tests, a tendency to over-prescribe antibiotics and a risk of antimicrobial resistance increase. However, a comprehensive understanding of acute pharyngitis management in emergency units is lacking. This study aimed to investigate the frequency of rapid antigen test use to diagnose acute pharyngitis, as well as other diagnostic approaches, the therapeutic attitude, and follow-up of children with this condition in the emergency units. Methods A multicentric national study was conducted in Italian emergency departments between April and June 2022. Results A total of 107 out of 131 invited units (response rate 82%), participated in the survey. The results showed that half of the units use a scoring system to diagnose pharyngitis, with the McIsaac score being the most commonly used. Most emergency units (56%) were not provided with a rapid antigen diagnostic test by their hospital, but the test was more frequently available in units visiting more than 10,000 children yearly (57% vs 33%, respectively, p = 0.02). Almost half (47%) of the units prescribe antibiotics in children with pharyngitis despite the lack of microbiologically confirmed cases of Group A β-hemolytic streptococcus. Finally, about 25% of units prescribe amoxicillin-clavulanic acid to treat Group A β-hemolytic streptococcus pharyngitis. Conclusions The study sheds light on the approach to pharyngitis in emergency units, providing valuable information to improve the appropriate management of acute pharyngitis in this setting. The routinary provision of rapid antigen tests in the hospitals could enhance the diagnostic and therapeutic approach to pharyngitis.